Effect Of Longeth Radiation And Temperature Shock Toward Ginogenesis Shealtfish (Ompok Rhadinurus Ng) - Ferry Dua Andhika; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted for 30 days from 29 October until 28 November 2013, in Hatchery and Fish Breeding Laboratory of Fisheries and Marine Sciences University of Riau. The aim of the study was to determine the effect of longeth radiation and heat shock differently toward ginogenesis shealtfish (Ompok rhadinurus Ng) fertilized by spermatozoa catfish (Pangasius hypophthalmus). The experiental used in this study with 2 factors and 10 treatments. The treatments were density of control hybridization and spermatozoa radiation with ultraviolet light (1, 2 and 3 minutes) and then performed for 1 minute after conception with heat shock 40°C (1, 2 and 3 minutes). The best treatment was 2 minutes while radiation performed for 1 minute after fertilization with heat shock of 40°C for 1 minutes (P2F1K1) with a success percentage of 95.67%. The water quality parameters along the research period were recoerded such as temperature 23-250 C, pH 5-6 and dissolved oxygen (DO) 5-7.5 mg/l respectively.Keywords : Ginogenesis, Long radiation, long heat shock, Ompok radhinurus Ng